PENDIDIKAN WANITA DALAM PERSPEKTIF KAUM FEMINIS - Fihris Fihris (Sawwa: Jurnal Studi Gender, 2015)
Education is a highly recommended in Islam, clearly Qur'an and hadith does not differentiate between men and women in providing educational opportunities. Both sexes are equally have rights and obligations in the scientific world. Acquisition of knowledge is a funda-mental right of every human being without distinction of sex. Thus, the general view of the Qur'an in terms of gender relations, in particular on the role and status of women, is very positive and constructive. Basically, the content and substance of the teachings of Islam is emphasized the spirit of equality and justice, the under-standing of this widely becoming a very urgent matter. Therefore it needs a thorough understanding of (univer-sal) in internalize the teachings of Islam so there will not arise any understanding and interpretation. A variety of data indicate how lame scientist male and female in the history of the Islamic world. There are a number of characters who are trying to think of women's educa-tion, but not enough to increase the quantity of educated women. Some figures in question is the feminist who thinks that women are entitled to the same education as men. Eventually this becomes a spectacular movement, both Islamic and Western feminists.